A study on the effectiveness of Customer Relationship Management (CRM) at Takaful Ikhlas Sdn Bhd / Norlela Abdul Halim - Abdul Halim, Norlela (Faculty of Business and Management, 2011)
This research conducted on the “The effectiveness of Customer relationship management (CRM) at Takaful Ikhlas Sdn. As a service company major in Takaful, Takaful Ikhlas Sdn Bhd realize that customer management are very important in order to built trust and satisfaction among their customers. The main objectives of this study are (1) to identify the level of effectiveness of Customer relationship management (CRM) at Takaful Ikhlas Sdn Bhd, (2) to identify the most influence factors of the effectiveness of Customer relationship management (CRM) at Takaful Ikhlas Sdn Bhd, (3) to identify the recommendation to the effectiveness of Customer relationship management (CRM) at Takaful Ikhlas Sdn Bhd. The respondent of this study were employee and loyal customer in Takaful Ikhlas SdnBhd. 100 questionnaires had been distributed among them. The researcher had used convenience sampling as sampling technique. The process of analyzing and interpreting data has been presented with tables using method as reliability test, frequency and descriptive analysis. The researcher also had come out with few recommendations can be taken into consideration. By implementing these recommendations, it will help Takaful Ikhlas Sdn Bhd to increase their reputation, better services and long-term profit with their loyal customers.